Biological aspects of two coexisting native and non-native fish species in the Aegean Sea: Pagellus erythrinus vs. Nemipterus randalli - YAPICI, SERCAN; FİLİZ, HALİT (Mediterranean Marine Science, 2019)
Nowadays, the Mediterranean is a hotspot of biodiversity, characterized by changes in fish communities due to invasions. These invasions, mainly occurring through the entrance of species through the Suez Canal, a process called Lessepsian migration, has been increasing in the last 40 years. It is reported that, in Turkish seas, where 512 fish species are found, are 75 Lessepsian species. However, knowledge about the impact of Lessepsian species on native species is insufficient. This study aims to determine the bio-ecological characteristics and food interactions of a native Pagellus erythrinus and non-native Nemipterus randalli distributed in the Gökova Bay. In the monthly sampling survey, carried out between January 2016 and December 2016, 1698 N. randalli and 945 P. erythrinus individuals were collected. Length, weight, age, sex distributions and ratios, length-age, weight-age, length-weight relationships, condition factors, stomach contents and reproduction periods were examined to determine the interaction between species. According to results, the life span of P. erythrinus is longer than N. randalli in the Gökova Bay. Nevertheless, N. randalli grows faster than P. erythrinus. Reproduction periods of both two species show similarities. Food competition between species is found to be significantly high. Results of condition factors exhibit that N. randalli shows an increased ability to exploit the available food sources. Pagellus erythrinus displays strategies such as: early maturation, short reproduction period, reproduction in the deeper waters and batch spawning, to compete with N. randalli. With the invasive characteristics of N. randalli established a successful population in the Gökova Bay.